KELAYAKAN DAN KEPRAKTISAN MODUL PRAKTIKUM TATA SURYA MENGGUNAKAN PAPER MERGE CUBE BERBASIS AUGMENTED REALITY - Maria Margareta Kwulo Kwuta; Adrianus Nasar; Ana Silfiani Rahmawati (OPTIKA: Jurnal Pendidikan Fisika, 2022)
This study aims to determine the feasibility and practicality of the solar system practicum module using augmented reality-based paper merge cube. The type of research used is development research with the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 3 validators consisting of 1 lecturer as a media expert and 2 subject teachers as material experts, as well as 20 students. The data obtained were expert validation and a questionnaire sheet for students. Data were analyzed using descriptive statistics. The results showed that the development of the solar system practicum module using a paper merge cube based on augmented reality had a very feasible category (82.3%) for content feasibility, a decent category (79.16) for language eligibility, and a very feasible category (87.5) for the feasibility of presentation, while the practicality of the module is in the very practical category (87.2%).